Mode of action and human relevance assessment of male CD‐1 mouse renal adenocarcinoma associated with lifetime exposure to empagliflozin. Issue 10 (18th April 2022) - Phillips, Jonathan A.; Taub, Mitchell E.; Bogdanffy, Matthew S.; Yuan, Jing; Knight, Brian; Smith, James D.; Ku, Warren W.
Abstract: Inhibition of sodium‐glucose cotransporter‐2 (SGLT2) has been shown to be a safe and efficacious approach to support managing Type 2 diabetes. In the 2‐year carcinogenicity study with the SGLT2 inhibitor empagliflozin in CD‐1 mice, an increased incidence of renal tubular adenomas and carcinomas was identified in the male high‐dose group but was not observed in female mice. An integrated review of available nonclinical data was conducted to establish a mode‐of‐action hypothesis for male mouse‐specific tumorigenesis. Five key events were identified through systematic analysis to form the proposed mode‐of‐action: (1) Background kidney pathology in CD‐1 mice sensitizes the strain to (2) pharmacology‐related diuretic effects associated with SGLT2 inhib ition. (3) In male mice, metabolic demand increases with the formation of a sex‐ and species‐specific empagliflozin metabolite. These features converge to (4) deplete oxidative stress handling reserve, driving (5) constitutive cellular proliferation in male CD‐1 mice. The proposed mode of action requires all five key events for empagliflozin to present a carcinogenicity risk in the CD‐1 mouse. Considering that empagliflozin is not genotoxic in the standard battery of genotoxicity tests, and not all five key events are present in the context of female mice, rats, or humans, nor for other osmotic diuretics or other SGLT2 inhibitors, the observed male mouse renal tumors are not considered relevant to humans. Abstract : Lack of SGLT1/SGLT2 selectivity, leading to calcium malabsorption specific to rodents, has been proposed as a mechanistic hypothesis linking rat carcinogenicity findings with SGLT2 inhibitors. This work presents an alternative key event sequence for empagliflozin, based on an integrated evidence assessment. Five key events are reviewed within a weight‐of‐evidence framework to establish a male mouse‐specific pathway to renal tumors following lifetime empagliflozin exposure.